POLA KOMUNIKASI KONSERVASI ANTARA LEMBAGA, MASYARAKAT, DAN MEDIA DALAM ISU PERLINDUNGAN SATWA LIAR DI DESA LEAHARY PULAU AMBON - Sahusilawane, John; Imlabla, Wilma (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Wildlife conservation necessitates strong communication methods between institutions, communities, and the media, as these three entities are vital in boosting public awareness and involvement in conservation initiatives. Commonly faced challenges consist of insufficient dialogic communication, restricted access to trustworthy information, and inadequate media portrayal in delivering conservation messages. This research seeks to examine the communication trends formed between institutions, communities, and the media, while also evaluating how these trends aid in wildlife conservation initiatives in Leahari Village. The study utilized a qualitative approach involving detailed interviews with ten carefully chosen informants, along with field observations and document examination. The results show that stakeholders communicate via seminars, campaigns, field activities, and social media; nonetheless, challenges persist, including low public engagement, the prevalence of entertainment-focused media, and insufficient educational resources. The community exhibits favorable reactions when communication is conveyed in a dialogic manner and connected to relatable local experiences. In summary, collaborative and organized conservation communication enhanced by innovative media use effectively boosts community awareness and aids in sustainable wildlife conservation initiatives